2013
DOI: 10.1186/1743-0003-10-81
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between non-neural and neural contributors to ankle joint stiffness in cerebral palsy

Abstract: BackgroundSpastic paresis in cerebral palsy (CP) is characterized by increased joint stiffness that may be of neural origin, i.e. improper muscle activation caused by e.g. hyperreflexia or non-neural origin, i.e. altered tissue viscoelastic properties (clinically: “spasticity” vs. “contracture”). Differentiation between these components is hard to achieve by common manual tests. We applied an assessment instrument to obtain quantitative measures of neural and non-neural contributions to ankle joint stiffness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 23 publications
(34 reference statements)
2
65
2
Order By: Relevance
“…It should also be pointed out that the short stretch we used may have prevented us from determining a contribution from stretch reflex activity that might have been elicited with a longer stretch resembling the clinical evaluation to a larger extent. Indeed, this could potentially explain why we, in contrast to other studies in which longer stretches were used (de Gooijer-van de Groep et al, 2013), did not observe reflex hyperexcitability in this patient group.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…It should also be pointed out that the short stretch we used may have prevented us from determining a contribution from stretch reflex activity that might have been elicited with a longer stretch resembling the clinical evaluation to a larger extent. Indeed, this could potentially explain why we, in contrast to other studies in which longer stretches were used (de Gooijer-van de Groep et al, 2013), did not observe reflex hyperexcitability in this patient group.…”
Section: Discussioncontrasting
confidence: 79%
“…It was therefore not surprising that neither of the two scales showed any correlation with reflex-mediated stiffness at rest in this patient population. This is somewhat in contrast to a recent study that reported a significantly larger reflex-mediated stiffness in 23 adolescents (range 12-19 years) with CP compared to an age-matched, healthy control group (de Gooijer-van de Groep et al, 2013). However, in that study a stretch of 30° lasting 250 ms was used.…”
Section: Discussioncontrasting
confidence: 69%
“…However, it is yet not defined what velocity and movement profile should be applied. In physical examination the movement profile is determined by constraints of human performance of the examiner, as opposed to motorized tests in which a particular movement profile can be imposed [40][41][42][43]. However, a motorized test is less feasible in clinical practice and constant velocities do not represent natural movement profiles [44].…”
Section: Further Directionsmentioning
confidence: 99%
“…Patients with CP develop muscle contractures that are thought to be multifactorial, including chronic muscle shortening (13) and decreased joint ROM (14) resulting in increased joint stiffness (15). The determinants of joint stiffness are (i) the passive component defined by the changes of the material properties of muscles and connective tissues, and (ii) the active component, which is the stiffness during dynamic conditions due to neural impairments (i.e., chronic muscle overactivity or spasticity) (16). Spasticity is believed to contribute to abnormal joint stiffness via changes of not only active but also passive muscle components due to adaptation (17).…”
mentioning
confidence: 99%